Optimal placement and sizing of renewable distributed generation via gravitational search algorithm - Daud, Sa’adah; Abdul Kadir, Aida Fazliana; Gan, Chin Kim; Abdullah, Abdul Rahim; Sulaima, Mohamad Fani; Shamsudin, Nur Hazahsha (Trans Tech Publications Ltd., 2015)
The installation of distributed generation (DG) gives advantages to the environment such as, it contribute in the reduction of non-peak operating cost, diversification of energy resources, lower losses thus improving overall organization. These advantages might be rescinded if no proper location and sizing of DGs are considered before the DG’s installation. This paper offers an optimal location and sizing of multiple DGs using heuristic method called gravitational search algorithm (GSA). The suggested algorithm is tested on 13-bus radial distribution system. This method is being compared with particle swarm optimization (PSO) in terms of system power loss, voltage deviation and total voltage harmonic distortion (THDv). GSA shows the ability to locate and sized DG optimally with a better performance and more reliable than PSO.